Creation of Batik Patterns on Scarves Inspired by the Remo Dance of East Java - Maya Dewi Puspita Sari; Deny Arifiana (KAMPUS AKADEMIK PUBLISING, 2026)
This study is a creative research project explaining the development of batik motifs and the design of batik scarves, presenting the final motifs, and describing the presentation of the scarves, all inspired by the Remo dance of East Java. The approach used is Practice-Led Research, comprising exploration, design, creation, and presentation. The exploration stage covered conceptualization, technical exploration, and material exploration. The design stage involved developing 10 alternative designs through stylized sketches and motif combinations. The creation stage included drawing the motifs, applying batik designs with a canting, dyeing, rinsing, drying, and sewing the fabric into scarves. The process resulted in three hand-drawn batik scarves Satria Remo 2, Satria Remo 4, and Satria Remo 8 created using stylized techniques. Satria Remo 2 highlights the